2017
DOI: 10.1021/acs.orglett.6b03801
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Total Synthesis of (+)- and (−)-Paeoveitol via a Hetero-Diels–Alder Reaction

Abstract: The first catalytic asymmetric total synthesis of (+)- and (-)-paeoveitol has been accomplished in 42% overall yield via a biomimetic hetero-Diels-Alder reaction. The chiral phosphoric acid catalyzed hetero-Diels-Alder reaction showed excellent diastereo- and enantioselectivity (>99:1 dr and 90% ee); two rings and three stereocenters were constructed in a single step to produce (-)-paeoveitol on a scale of 452 mg. This strategy enabled us to selectively synthesize both paeoveitol enantiomers from the same subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Chen group reported the first catalytic asymmetric total synthesis of (+)‐ and (−)‐paeoveitol via a biomimetic hetero‐Diels–Alder reaction with chiral SPA 3 (Scheme 98). [ 102 ] The key feature of the total synthesis is the chiral SPA‐catalyzed asymmetric hetero‐ Diels−Alder reaction of paeoveitol D and O‐quinone methoide to provide the excellent diastereo‐ and enantioselectivity (>99 : 1 dr and 90% ee) and synthesize both paeoveitol enantiomers from the same substrates by simply changing the catalyst's stereochemistry.…”
Section: Application In Total Synthesismentioning
confidence: 99%
“…Chen group reported the first catalytic asymmetric total synthesis of (+)‐ and (−)‐paeoveitol via a biomimetic hetero‐Diels–Alder reaction with chiral SPA 3 (Scheme 98). [ 102 ] The key feature of the total synthesis is the chiral SPA‐catalyzed asymmetric hetero‐ Diels−Alder reaction of paeoveitol D and O‐quinone methoide to provide the excellent diastereo‐ and enantioselectivity (>99 : 1 dr and 90% ee) and synthesize both paeoveitol enantiomers from the same substrates by simply changing the catalyst's stereochemistry.…”
Section: Application In Total Synthesismentioning
confidence: 99%
“…Paeoveitol is one of the main antipsychotic components of Radix Paeoniae Rubra. [30][31] In 2017, Chen Jijun's group reported for the first time the enantioselective 6-step total synthesis of Paeoveitol with an overall yield of 42% [32], and the best result was the 7-step total synthesis published by Xie Zhixiang's group with an overall yield of 26% [33]. SPA catalyzed hetero Diels alter reaction, as a key step, provides high yield (up to 95%) and good corresponding selectivity (up to 90% ee).…”
Section: Introductionmentioning
confidence: 99%
“…[12] Furthermore, QMs also react with electron-rich alkenes in the Diels-Alder reaction and give chromane products, [5] and this techniquew as recently exploitedi nt he synthesis of complex molecular structures. [13][14][15][16][17][18] Particularly importanti st he reactivity of QMs with biologically relevantn ucleophilesi ncluding amino acids, [19] proteins, [20,21] nucleobases [22] and DNA, [23][24][25][26] and G-quadruplex structures. [27][28][29][30] Moreover,R okita et al demonstrated that QMs reacteda sr eversible DNA cross-linking DNA agents, [31][32][33] which was connected to the biological action of some anticancer antibiotics such as mitomycine.…”
Section: Introductionmentioning
confidence: 99%
“…Electrophiles (e.g., H + ) attack the carbonyl oxygen atom, whereas the exocyclic methylene position is prone to attack by nucleophiles that in a Michael addition react with QMs . Furthermore, QMs also react with electron‐rich alkenes in the Diels–Alder reaction and give chromane products, and this technique was recently exploited in the synthesis of complex molecular structures . Particularly important is the reactivity of QMs with biologically relevant nucleophiles including amino acids, proteins, nucleobases and DNA, and G‐quadruplex structures .…”
Section: Introductionmentioning
confidence: 99%